Primary mandibular first molar with single root and single canal: a case report of a rare morphology. - Zahra Bahrololoomi; Roya Ghafourifard; Ali Asghar Soleimani (Frontiers in Dentistry, 2014)
Single rooted primary mandibular first molar is a rare developmental anomaly. Literatures reveal that failure of invagination of Hertwig's epithelial root sheath leads to this unusual root form. Thorough knowledge of root canal morphology and anatomical variations of primary teeth can help a pediatric dentist in successful root canal treatment. Hereby, we describe two cases of primary mandibular first molars with an unusual morphology as a single root called pyramidal molar.